2019
DOI: 10.1002/pen.25154
|View full text |Cite
|
Sign up to set email alerts
|

Properties of microinjection‐molded polypropylene/graphite composites

Abstract: In this study, polypropylene (PP) composites filled with two different types of graphite particles, that is, flake‐shaped synthetic graphite (SG) and low‐temperature expandable graphite (LTEG), were prepared by melt blending, followed by microinjection molding (μIM). The microparts had three consecutive zones with decreasing thickness along the flow direction (FD). Results showed that, in addition to the larger particle size, the in situ exfoliation of LTEG during melt processing is crucial to the overall enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…As shown in Table 3, the crystallization behavior was significantly expedited with the presence of CNT, and the values of T c increased with increasing CNTs concentration. The above results suggested that a strong heterogeneous nucleation effect occurred and the crystallization process was dependent on the number of the added fillers, which was consistent with literature 39–41 . Additionally, when compared with pure H‐PP, the χ c of H‐PP/CNT composites from both heating cycles (i.e., Cycle 1 and Cycle 3) decreased with increasing filler concentrations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Table 3, the crystallization behavior was significantly expedited with the presence of CNT, and the values of T c increased with increasing CNTs concentration. The above results suggested that a strong heterogeneous nucleation effect occurred and the crystallization process was dependent on the number of the added fillers, which was consistent with literature 39–41 . Additionally, when compared with pure H‐PP, the χ c of H‐PP/CNT composites from both heating cycles (i.e., Cycle 1 and Cycle 3) decreased with increasing filler concentrations.…”
Section: Resultssupporting
confidence: 89%
“…The above results suggested that a strong heterogeneous nucleation effect occurred and the crystallization process was dependent on the number of the added fillers, which was consistent with literature. [39][40][41] Additionally, when compared with pure H-PP, the χ c of H-PP/CNT composites from both heating cycles (i.e., Cycle 1 and…”
Section: Rheologymentioning
confidence: 99%
“…Furthermore, the authors accorded special attention to the polymer composite materials because of their large potential for use and commercialization. Therefore, the influence of the machine processing parameters on morphology, electrical, and mechanical properties of microinjection molded parts filled with nanotube composites material was intensively investigated 12‐16 . The special mold insert helps to distinguish the melting behavior when flowing across three part‐steps with decreasing thickness, considering the severe shearing conditions that prevail in the microinjection molding process.…”
Section: Research Backgroundmentioning
confidence: 99%